Fiscal behaviour in the European Union: rules, fiscal decentralization and government indebtedness - António Afonso; Sebastian Hauptmeier (European Central Bank (ECB), 2009)
We assess the fiscal behaviour in the European Union countries for the period 1990-2005 via the responsiveness of budget balances to several determinants. The results show that the existence of effective fiscal rules, the degree of public spending decentralization, and the electoral cycle can impinge on the country's fiscal position. Furthermore, the results also support the responsiveness of primary balances to government indebtedness.
Keywords: C23; E62; H62; 330; European Union; fiscal decentralization; fiscal regimes; fiscal rules; panel data; Öffentlicher Haushalt; Haushaltsdefizit; Finanzpolitik; Dezentralisierung; Politischer Konjunkturzyklus; Panel; EU-Staaten